Relationship of Psychological Characteristics to Daily Life Ischemia: An Analysis From the National Heart, Lung, and Blood Institute Psychophysiological Investigations in Myocardial Ischemia. Issue 3 (24th April 2022) - Dasa, Osama; Mahmoud, Ahmed N.; Kaufmann, Peter G.; Ketterer, Mark; Light, Kathleen C.; Raczynski, James; Sheps, David S.; Stone, Peter H.; Handberg, Eileen; Pepine, Carl J.
ABSTRACT: Objective: Cardiac ischemia during daily life is associated with an increased risk of adverse outcomes. Mental stress is known to provoke cardiac ischemia and is related to psychological variables. In this multicenter cohort study, we assessed whether psychological characteristics were associated with ischemia in daily life. Methods: This study examined patients with clinically stable coronary artery disease (CAD) with documented cardiac ischemia during treadmill exercise ( n = 196, mean [standard deviation] age = 62.64 [8.31] years; 13% women). Daily life ischemia (DLI) was assessed by 48-hour ambulatory electrocardiophic monitoring. Psychological characteristics were assessed using validated instruments to identify characteristics associated with ischemia occurring in daily life stress. Results: High scores on anger and hostility were common in this sample of patients with CAD, and DLI was documented in 83 (42%) patients. However, the presence of DLI was associated with lower anger scores (odds ratio [OR] = 2.03; 95% confidence interval [CI] = 1.12–3.69), reduced anger expressiveness (OR = 2.04; 95% CI = 1.10–3.75), and increased ratio of anger control to total anger (OR = 2.33; 95% CI = 1.27–4.17). Increased risk of DLI was also associated with lower hostile attribution (OR = 2.22; 95% CI = 1.21–4.09), hostile affect (OR = 1.92; 95% CI = 1.03–3.58), and aggressive responding (OR = 2.26; 95% CI = 1.25–4.08). We observed weak inverse correlations between DLI episode frequency and anger expressiveness, total anger, and hostility scores. DLI was not associated with depression or anxiety measures. The combination of the constructs low anger expressiveness and low hostile attribution was independently associated with DLI (OR = = 2.59; 95% CI = 1.42–4.72). Conclusions: In clinically stable patients with CAD, the tendency to suppress angry and hostile feelings, particularly openly aggressive behavior, was associated with DLI. These findings warrant a study in larger cohorts, and intervention studies are needed to ascertain whether management strategies that modify these psychological characteristics improve outcomes.